Understanding and characterizing the services sector in South Africa: An overview - Haroon Bhorat; François Steenkamp; Christopher Rooney; Nomsa Kachingwe; Adrienne Lees (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The South African services sector is large and growing. This coupled with declining employment shares in manufacturing and mining (i.e. deindustrialization) suggests that South Africa is a de facto service-orientated economy. Employment patterns in services reveal a segmentation that is characterized by high-productivity, high-wage services, low-productivity, low-wage services, and government services. There has been sustained growth in services exports in the post-1994 period but the composition is biased toward traditional services. Increased entry into developing country markets is characterized by increasingly sophisticated services. A key driver of export growth is the expansion of foreign direct investment into developed country markets, and increasingly, into developing country markets, particularly African markets.
Keywords: L80; O14; O55; 330; services; economic development; South Africa; economic growth; structural change